Nonlinear Fractional Differential Equations of Variable Order - Souid, Mohammed Said; İnç, Mustafa; Benkerrouche, Amar (CRC Press, 2026)
The book explores the theory and applications of fractional differential equations with variable order. It delves into the mathematical foundations, including notations, definitions, and key theorems, while also addressing practical applications in various fields. The book will guide readers from basic concepts to advanced topics, making it suitable for both researchers and graduate students in mathematics, engineering, and applied sciences. Each chapter includes illustrative examples and numerical applications to reinforce theoretical concepts. The book also emphasizes stability analysis and the use of fixed-point theorems in solving fractional differential equations. © 2026 Mohammed Said Souid, Mustafa Inc, and Amar Benkerrouche.
Keywords: Differential equations; Students; Basic concepts; Engineering and Applied Science; Fixed points theorems; Fractional differential equations; Graduate students; Mathematical foundations; Nonlinear fractional differential equations; Numerical applications; Stability analyze; Variables ordering; Nonlinear equations